CEREBRAL OXIMETRY USE FOR CARDIAC SURGERY - Raza, Syed Shahmeer; Ullah, Farhan; ., Chandni; Savage, Edward Bruce (Journal of Ayub Medical College Abbottabad, 2017)
Background: Studies have shown maintaining good cerebral perfusion during Cardiac Surgeries is very important in terms of patient outcomes and reducing the hospital stay, which may have its financial and clinical implications. The aim of this review study was to determine the effectiveness of Cerebral Oximetry (Transcranial Near-Infrared Spectroscopy-NIRS to monitor cerebral oxygenation) for Cardiac Surgery and to propose a possible concluding remark about its potential applications, overall clinical value and whether to keep using it or not. Methods: Medical database and archives including Pubmed, Embase, index medicus, index copernicus and Medline were searched. Different papers were looked upon and each had an argument, scientific evidence and background. Fifteen research papers were selected and brought under review after carefully consideration. Results: The papers were carefully reviewed and findings were given in favour of not using NIRS technique for Cerebral Oximetry in Cardiac Surgery. Conclusion: This can rightly be concluded from this study that NIRS Cerebral Oximetry does not carry the clinical significance and relevance which was previously thought. The subject under observation needs further studies and research to evaluate the effectiveness of the Cerebral Oximetry Use for Cardiac Surgery. Keywords: NIRS; cerebral oximetry; cerebral perfusion